Concomitant Bacteremia in Adults With Severe Falciparum Malaria. (28th February 2020) - Phu, Nguyen Hoan; Day, Nicholas P J; Tuan, Phung Quoc; Mai, Nguyen Thi Hoang; Chau, Tran Thi Hong; Van Chuong, Ly; Vinh, Ha; Loc, Pham Phu; Sinh, Dinh Xuan; Hoa, Nguyen Thi Tuyet; Waller, Deborah J; Wain, John; et al.
Abstract: Background: Approximately 6% of children hospitalized with severe falciparum malaria in Africa are also bacteremic. It is therefore recommended that all children with severe malaria should receive broad-spectrum antibiotics in addition to parenteral artesunate. Empirical antibiotics are not recommended currently for adults with severe malaria. Methods: Blood cultures were performed on sequential prospectively studied adult patients with strictly defined severe falciparum malaria admitted to a single referral center in Vietnam between 1991 and 2003. Results: In 845 Vietnamese adults with severe falciparum malaria admission blood cultures were positive in 9 (1.07%: 95% confidence interval [CI], .37–1.76%); Staphylococcus aureus in 2, Streptococcus pyogenes in 1, Salmonella Typhi in 3, Non-typhoid Salmonella in 1, Klebsiella pneumoniae in 1, and Haemophilus influenzae type b in 1. Bacteremic patients presented usually with a combination of jaundice, acute renal failure, and high malaria parasitemia. Four bacteremic patients died compared with 108 (12.9%) of 836 nonbacteremic severe malaria patients (risk ratio, 3.44; 95% CI, 1.62–7.29). In patients with >20% parasitemia the prevalence of concomitant bacteremia was 5.2% (4/76; 95% CI, .2–10.3%) compared with 0.65% (5/769; 0.08–1.2%) in patients with <20% parasitemia, a risk ratio of 8.1 (2.2–29.5). Conclusions: In contrast to children, the prevalence of concomitant bacteremia in adults with severe malaria is low. Administration of empirical antibiotics, in addition to artesunate, is warranted in the small subgroup of patients with very high parasitemias, emphasizing the importance of quantitative blood smear microscopy assessment, but it is not indicated in most adults with severe falciparum malaria. Abstract : Blood cultures were positive in 9 of 845 sequentially studied Vietnamese adults with severe falciparum malaria. In contrast to children, concomitant bacteremia in adults with severe malaria is uncommon and does not warrant use of empirical antibiotics in all patients.